Software design and development concepts, methodologies, tools, and applications - IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2014)
'This reference brings together the best practices and points of view on both theory and practice for the development of software systems, providing the latest knowledge on the techniques, applications, and methodologies for the design and development of software systems'--Provided by publisher.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 16, 2013).
Keywords: Computer software -- Development; Consumer electronics; decision support systems; Global collaborative systems; Information systems; Software design; Systems engineering